2010
DOI: 10.1101/lm.1859810
|View full text |Cite
|
Sign up to set email alerts
|

Switching from contextual to tone fear conditioning and vice versa: The key role of the glutamatergic hippocampal-lateral septal neurotransmission

Abstract: International audienceThe aim of the present experiment was to directly assess the role of the glutamatergic hippocampal-lateral septal (HPC-LS) neurotransmission in tone and contextual fear conditioning. We found that pretraining infusion of glutamatergic acid into the lateral septum promotes tone conditioning and concomitantly disrupts contextual conditioning. Infusion of glutamatergic antagonist, on the contrary, promotes contextual conditioning to the detriment of tone fear conditioning. These findings hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 24 publications
6
21
0
1
Order By: Relevance
“…Further experiments involving glutamate agonists and antagonists injected into LS prior to training further support this idea (Calandreau et al 2010). In these experiments, injection of glutamate agonists into LS promoted auditory fear conditioning and disrupted context fear conditioning, whereas the glutamate antagonists had the opposite effect (Calandreau et al 2010). These findings thus suggest that the LS plays a key role in the specificity of fear conditioning, via selection of the relevant stimuli.…”
Section: Lateral Septumsupporting
confidence: 54%
See 1 more Smart Citation
“…Further experiments involving glutamate agonists and antagonists injected into LS prior to training further support this idea (Calandreau et al 2010). In these experiments, injection of glutamate agonists into LS promoted auditory fear conditioning and disrupted context fear conditioning, whereas the glutamate antagonists had the opposite effect (Calandreau et al 2010). These findings thus suggest that the LS plays a key role in the specificity of fear conditioning, via selection of the relevant stimuli.…”
Section: Lateral Septumsupporting
confidence: 54%
“…These results suggest a specificity of involvement of LS in auditory, or possibly different forms of cued conditioning, over context conditioning. Further experiments involving glutamate agonists and antagonists injected into LS prior to training further support this idea (Calandreau et al 2010). In these experiments, injection of glutamate agonists into LS promoted auditory fear conditioning and disrupted context fear conditioning, whereas the glutamate antagonists had the opposite effect (Calandreau et al 2010).…”
Section: Lateral Septummentioning
confidence: 61%
“…Nevertheless, they also unveiled a more extended role for the hippocampus in fear conditioning. Indeed, our data repeatedly and consistently showed that the hippocampus is differentially engaged in fear conditioning depending on the predictive value of CSs (Calandreau et al, 2005(Calandreau et al, , 2006(Calandreau et al, , 2007(Calandreau et al, , 2010Desmedt et al, 1998Desmedt et al, , 1999. As written above, subjects adaptively select among environmental stimuli those that best predict an aversive event, either a discrete CS when it is paired with, and thus predictive of, the aversive US, or the context when a CS-US unpairing procedure is used.…”
Section: The Classical Role Of the Hippocampus In Fear Memorymentioning
confidence: 69%
“…In accordance with previous electrophysiological data, we showed that pretraining infusion of glutamic acid into the lateral septum, which mimics an increase in the HPC-LS neurotransmission, promotes the selection of a discrete tone CS to the detriment of the context as predictor of a footshock US. In contrast, infusion of glutamatergic antagonist (Kynurenate), which inhibits this neurotransmission, promotes the selection of the context as major predictor of the US, while blocking the identification of the discrete tone CS as predictor (Calandreau et al, 2010). In full accordance with these data, we had previously shown that pre-training infusion of arginine vasopressin or its antagonist into the lateral septum, which are known to indirectly modulate the HPC-LS glutamatergic neurotransmission, could also promote the selection of the discrete tone CS or the context, respectively, as predictor of the US (Desmedt et al, 1999).…”
Section: The Classical Role Of the Hippocampus In Fear Memorymentioning
confidence: 92%
See 1 more Smart Citation